Instrumen Zakat Sebagai Sumber Penerimaan dan Pengeluaran Keuangan Negara - Onti Laura Citra; Yuyun Yuniara; Idia Jonionda Piolita; Andi Cahyono (Al-Khair Journal: Management Education, 2023)
Abstract“This study discusses the essence of zakat as an Islamic financial instrument in the view of Muhammad Nejatullah Siddiqi. The results of this study show that Muhammad Nejatullah Siddiqi is one of the contemporary Islamic economists from the mainstream class. Thoughts about zakat are always related to Islamic economics. Zakat is the obligation of the rich, the right of the poor, and the state has an important role in managing it. It contains moral, social, and economic aspects. Zakat is the axis and center of state finance. Its position on the one hand can be a potential source of poverty alleviation, on the other hand it can be a working capital for the poor so they can open up jobs. It can even be used as the last shield for the economy so that it does not sink when consumption capacity stagnates. Keywords; Muhammad Nejatullah Siddiqi, Zakat, and Islamic Economics Abstrak“Studi  ini  membahas tentang  esensi  zakat  sebagai  instrumen  finansial Islami  dalam  pandangan  Muhammad  Nejatullah  Siddiqi.  Hasil  studi  ini memperlihatkan  bahwa Muhammad  Nejatullah  Siddiqi  merupakan  salah satu  ekonomi  Islam  kontemporer  dari  golongan  mainstrem.  Pemikiran tentang  zakat senantiasa  terkait  dengan  ekonomi  Islam. Zakat  merupakan kewajiban   orang-orang   kaya,   hak   orang-orang   miskin,   dan   negara mempunyai    peran    penting    dalam    pengelolaannya. Di    dalamnya mengandung  aspek  moral,  sosial,  dan  ekonomi. Zakat adalah  poros  dan pusat  keuangan  negara.  Kedudukannya satu  sisi  dapat  menjadi  sumber potensial  untuk  mengentaskan  kemiskinan  di  sisi  lain  dapat  menjadi  modal kerja bagi orang miskin agar dapat membuka lapangan pekerjaan. Bahkan dapat dipergunakan sebagai perisai terakhir bagi perekonomian agar tidak terpuruk ketika kemampuan konsumsi mengalami stagnasi. Kata Kunci; Muhammad Nejatullah Siddiqi, Zakat, dan Ekonomi Islam